Determinants of current account imbalance in the global economy: A dynamic panel analysis - Debasish Kumar Das (Journal of Economic Structures, 2016)
This paper presents an empirical investigation of the determinants of current account imbalance for the large sample of developed, emerging and developing countries during 1980-2011. Using dynamic panel GMM techniques, this study characterizes that current account balance is positively correlated with net foreign assets, trade openness and exchange rate stability and negatively associated with commodity price, real GDP growth and real effective exchange rate for the developed countries. While, among emerging countries, commodity price, real GDP growth, trade openness and de jure capital openness are positively correlated with net foreign asset, exchange rate stability index is negatively related to current account balance. These findings suggest that the current account determinants explain different characteristics in terms of different country groups.
Keywords: F62; F30; C33; 330; Current account determinants; Global imbalance; Dynamic panel GMM